Different molecular weights chitosan coatings delay the senescence of postharvest nectarine fruit in relation to changes of redox state and respiratory pathway metabolism. (15th August 2019) - Zhang, Wanli; Zhao, Handong; Zhang, Jing; Sheng, Zhongting; Cao, Jiankang; Jiang, Weibo
Graphical abstract: Highlights: Low molecular (LM) and high molecular (HM) weight chitosan delayed nectarine senescence postharvest. LM and HM chitosan both enhanced the antioxidant system. Fruit treated with HM chitosan manifested better quality and redox state than LM. HM chitosan coating severely affected respiratory pathway metabolism. Abstract: The aim of this study is to investigate the impact of different molecular weights of chitosan treatment (LM 30 kDa; HM 120 kDa) on fruit senescence related to redox state and respiratory pathway metabolism in postharvest nectarine fruit stored at 25 °C for 8 days. The treatments of LM and HM chitosan both delayed senescence, which are due to inhibition of respiration rate, and enhanced the antioxidant system, as evidenced by the improvement of ASA-GSH cycle and total phenolics and flavonoids contents and decrease in H2 O2 and MDA accumulation. Meanwhile, fruit treated with HM chitosan manifested better quality and redox state than LM. It is noteworthy that the results showed that HM chitosan notably suppressed the activity of SDH enzyme and increased the total activity of G-6-PDH and 6-PGDH. Accordingly, changed respiratory pathways by HM chitosan coating contributed to senescence retardation and modification of redox status in postharvest nectarine fruit.